Film‐Based Implants for Supporting Neuron–Electrode Integrated Interfaces for The Brain. (18th November 2013) - Tang‐Schomer, Min D.; Hu, Xiao; Hronik‐Tupaj, Marie; Tien, Lee W.; Whalen, Michael J.; Omenetto, Fiorenzo G.; Kaplan, David L.
<x xml:space="preserve">Abstract</x> Neural engineering provides promise for cell therapy by integrating the host brain with brain–machine‐interface technologies in order to externally modulate functions. Long‐term interfaces with the host brain remain a critical challenge due to insufficient graft cell survivability and loss of brain electrode sensitivity over time. Here, integrated neuron–electrode interfaces are developed on thin flexible and transparent silk films as brain implants. Mechanical properties and surface topography of silk films are optimized to promote cell survival and alignment of primary rat cortical cells. Compartmentalized neural cultures and co‐patterned electrode arrays are incorporated on the silk films with built‐in wire connections. Electrical stimulation via electrodes embedded in the films activated surrounding neurons to produce evoked calcium responses. In mice brains, silk film implants show conformal contact capable of modulating host brain cells with minimal inflammatory response and stable indwelling for weeks. The approach of combining cell therapy and brain electrodes could provide sustained functional interfaces with ex vivo control with spatial precision.